Macroeconomic dynamics and the long-run equilibrium analysis of the 4Is in import-dependent countries: how is the past different from the present? - Deodat E. Adenutsi; Christian R.K. Ahortor; Johnson W. Ahiadorme (Cogent Economics & Finance, 2025)
This paper investigates the macroeconomic interplay of income, inflation, investment, and import-dependence (the 4Is) in import-dependent countries, comparing trends from 1966–1999 to 2000–2022. Using Panel Autoregressive Distributed Lag (ARDL) analytical framework, it identifies empirical relationships among the 4Is over two periods: pre-Millennium era (1966–1999) and the Millennium era (2000–2022). It reveals a nuanced interaction where import dependency detrimentally affects investment alongside neutral income growth and inflation effects, especially in the Millennium era. Results suggest monetary policy and supply-side reforms could enhance economic stability and growth, calling for reduced import reliance, controlled inflation, and incentivised domestic production to bolster long-term economic prosperity in these countries. It emphasises the post-2000 shift towards more stable macroeconomic environments and decreased import dependence, reflecting global economic changes and policy shifts towards inflation targeting. Policy recommendations focus on managing inflation, boosting domestic production, and fostering investment to mitigate the negative impacts of import dependence and support sustainable economic growth. The study contributes empirical evidence highlighting the vulnerability of such economies to imported inflation and the consequences of heavy import reliance, such as diminished production and lower income.